Hierarchical nanoparticle-induced superhydrophilic and under-water superoleophobic Cu foam with ultrahigh water permeability for effective oil/water separation. Issue 27 (23rd June 2016) - Luo, Zhi-Yong; Chen, Kai-Xuan; Wang, Jun-Hui; Mo, Dong-Chuan; Lyu, Shu-Shen
Abstract : Superhydrophilic Cu foam (SCuF) that consists of oxy-chloridized hierarchical nanoparticles is first synthesized for effective oil/water separation. Abstract : In recent years, Cu foam has attracted intensive attention owing to its remarkable performance for oil/water separation. Most research has mainly focused on Cu foam with surfactant decoration, which results in superhydrophobic or even stimuli-responsive membranes. Fabricating Cu foam with intrinsic superhydrophilicity via simple operations still remains a challenge. Herein, we synthesized superhydrophilic and under-water superoleophobic Cu foam that consists of oxy-chloridized hierarchical nanoparticles with metal Cu cores and polar Cu2 O/CuO1− x /2 Cl x shells via the combination of anodization, HCl etching and calcination. This material shows ultrahigh water permeability (5 μl water-droplet permeating within 9 ms). The oil/water separation efficiency of superhydrophilic Cu foam (SCuF) is above 99% with the oil content in separated water lower than 3 ppm. Moreover, the oil/water separation performance of SCuF for repeated use and anti-corrosion is also excellent. To the best of our knowledge, it is the first attempt to synthesize intrinsic superhydrophilic Cu foam for effective oil/water separation. Due to the greatly enhanced specific surface area and active sites, it has potential applications in catalysis, hydrogen evolution processes, electrode materials and many other environmental protection and energy fields.